Deliverability Test Analysis on Gas Well YA-01 - Ristawati, Arinda; Ginting, Mulia; Kaynes , Jasmine Ghina; Prapansya , Onnie Ridaliani; Oetomo , Hari Karyadi (LPPM Institut Teknologi Petroleum Balongan, 2024)
Deliverability tests are used to evaluate a well's production capability by estimating the Absolute Open Flow Potential (AOFP) and maximum flow rate. The three main methods applied are the Flow-after-flow Test, Isochronal Test, and Modified Isochronal Test. For the YA-01 gas well, the Flow-after-flow Test was used, which involves steps such as data compilation, plotting, calculation of the inverse slope (n), and determination of the AOFP and maximum flow rate (Qmax). Software analysis results indicated an inverse slope (n) of 1.19226, a C value of 0.000000418 MSCFD/psia², an AOFP of 12,930 MSCFD, and a Qgmax of 3,879 MSCFD. For verification, a manual analysis using the Rawlins-Schellhardt and Horner methods with a pseudo-pressure approach was conducted, yielding an AOFP value of 12,850 MSCFD. The combination of software and manual results provides a comprehensive and accurate understanding of the well conditions, supporting production optimization decisions and evaluating the effectiveness of the acidizing process.